2012
DOI: 10.1371/journal.pone.0040171
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Door Handle Design and Their Contamination with Bacteria: A Real Life Observational Study. Are We Pulling against Closed Doors?

Abstract: ObjectiveTo determine whether microbial contamination of door handles in two busy intensive care units and one high dependency unit was related to their design, location, and usage.DesignObservational study of the number of viable bacteria on existing door handles of different design at defined entry/exit points with simultaneous data collection of who used these doors and how often.SettingTwo busy specialised intensive care units and one high dependency unit in a tertiary referral NHS neurological hospital.Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 14 publications
3
21
1
1
Order By: Relevance
“…One recent observational study examined the number of viable bacteria found on hospital door handles of different designs in certain high traffic areas in a tertiary referral hospital in the UK. The authors found that the door handle's location, design and mode of use were all factors that affected their degree of contamination, with the traditional lever-style handles being the most highly contaminated [25].…”
Section: Discussionmentioning
confidence: 99%
“…One recent observational study examined the number of viable bacteria found on hospital door handles of different designs in certain high traffic areas in a tertiary referral hospital in the UK. The authors found that the door handle's location, design and mode of use were all factors that affected their degree of contamination, with the traditional lever-style handles being the most highly contaminated [25].…”
Section: Discussionmentioning
confidence: 99%
“…126 On average, a fall cost the NHS £73.33. 128 These claims cost over £3M in compensation. However, it is difficult to estimate the cost of a single claim after a fall (unitary claim).…”
Section: The Costs Associated With Fallsmentioning
confidence: 99%
“…This supports Dowdeswell et al, 8 who suggest that good infection control practices, such as access to hand washing facilities and hand hygiene, are more important factors in reducing HCAI rates than single rooms per se (cf. Wojgani et al 128 ), although compliance may be facilitated by careful design and location in a single room, along with toilets that are not shared between patients. Certainly the evidence here cannot be interpreted as providing generalisable evidence that single rooms play no part in the control of infection.…”
Section: Introductionmentioning
confidence: 99%
“…The latter was most probably due to variation in cleaning practices and the frequency of touching; higher bacterial loads have been found with frequent use of, for example, door handles (Wojgani et al . ). Copper surfaces instead showed similar low <12 CFU cm −2 average bacterial counts in all facilities excluding office toilet flush buttons and retirement home floor drain lids (Table ).…”
Section: Resultsmentioning
confidence: 97%
“…However, increased bacterial counts >73 CFU cm À2 and high variability existed on reference toilet flush buttons in office and hospital, which was particularly evident for the retirement home door handle references ( Table 2). The latter was most probably due to variation in cleaning practices and the frequency of touching; higher bacterial loads have been found with frequent use of, for example, door handles (Wojgani et al 2012). Copper surfaces instead showed similar low <12 CFU cm À2 average bacterial counts in all facilities excluding office toilet flush buttons and retirement home floor drain lids ( Table 2).…”
Section: Resultsmentioning
confidence: 99%